Comparison of Mini-Midvastus and Conventional Total Knee Arthroplasty with Clinical and Radiographic Evaluation: A Prospective Randomized Clinical Trial with 5-Year Follow-up. (15th June 2016) - Verburg, Hennie; Mathijssen, Nina M.C.; Niesten, Dieu-Donné; Verhaar, Jan A.N.; Pilot, Peter
Abstract : Background: The main objective of this prospective randomized study was to compare the clinical and radiographic outcomes of the mini-midvastus (MMV) approach with the conventional approach for total knee arthroplasty at the 5-year follow-up. Methods: Ninety-seven patients (100 knees) with osteoarthritis were assigned to the MMV group or to a group receiving conventional total knee arthroplasty. Intraoperative and postoperative clinical data were collected. At 6 weeks and at 1, 2, and 5 years postoperatively, the Knee Injury and Osteoarthritis Outcome Score (KOOS), the Oxford Knee Score (OKS), the Knee Society Score (KSS), and the Short Form (SF)-12 were completed. Radiographs of the knee were made preoperatively and at 1 day and 1 and 5 years postoperatively. Computed tomography (CT) scans were performed 2 years postoperatively. Results: In the MMV group, the mean skin incision was 2.5 cm shorter (p < 0.001) and the mean duration of the operation was 6 minutes longer than in the conventional total knee arthroplasty group (p < 0.05). Eight patients in the conventional group had a lateral parapatellar retinacular release compared with 1 in the MMV group; the difference was significant (p = 0.01). Three intraoperative complications, including 2 small lateral femoral condylar fractures and 1 partial patellar tendon laceration, occurred in the MMV group. Seven patients in the MMV group had postoperative blisters; all of them had a relatively large femoral component and 4 of them were large men. The radiographs and CT scans of the prostheses showed no significant differences between the MMV and conventional groups except for the posterior slope of the tibial component. In addition, no significance differences were detected between the groups with respect to the KOOS, OKS, KSS, and SF-12 scores determined at the 6-week and the 1, 2, and 5-year follow-up evaluations. Conclusions: In the rehabilitation period and at the short and mid-term follow-up, no relevant clinical and radiographic differences were found between the MMV and the conventional approach for total knee arthroplasty, making the advantage of MMV total knee arthroplasty cosmetic. We discourage the use of the MMV approach in large male patients because of the increased number of intraoperative complications and skin blisters postoperatively. Level of Evidence: TherapeuticLevel I . See Instructions for Authors for a complete description of levels of evidence.